A New Approach to Curriculum Development: The Relevance of the Higher Education Curriculum to Industry Needs - Ardhana Januar Mahardhani; Bernadetha Nadeak; Ita Musfirowati Hanika; Izlan Sentryo; Rosmalina Kemala (PT Inovasi Pratama Internasional, 2023)
The relevance of higher education curricula to the evolving needs of industry is key to providing students with the skills and knowledge they need. A new approach to curriculum development is needed, which includes several important aspects. First, the relevance of the curriculum must be placed in a broader social context, taking into account the social impact and contribution of students to society. Project-based learning is also emerging as an effective model, involving students in research or problem-solving projects that provide real-world experience. The importance of formative assessment as a tool for providing feedback that helps students improve their understanding is also highlighted. Involving students as active partners in curriculum development can create greater engagement. The curriculum must be able to accommodate student diversity and promote inclusivity. A competency-based approach emphasizes the development of practical skills that are relevant to the real world. A curriculum that is responsive to industry changes provides graduates with skills that increase their competitiveness in the job market. Close collaboration with industry is a key factor in ensuring curriculum relevance. Continuous evaluation, industrial training for lecturers, and flexibility in the curriculum are important strategies. The relevance of the curriculum is the key to creating graduates who are ready to face the ever-growing world of work and contribute to industrial innovation. This approach recognizes the importance of renewal and relevance in higher education to produce graduates who are ready to face changes in the ever-evolving world of work. This is a challenge and opportunity to create future leaders who innovate, are open-minded, and able to adapt to rapid changes in the dynamic world of work. In the era of globalization and technological development, the relevance of higher education curricula is becoming increasingly important to ensure graduates have relevant skills.